The Predictive Significance of Platelet‐to‐Lymphocyte Ratio for Miscarriage: A Systematic Review and Meta‐Analysis - Xiaoyi Wang; Yanfang Zhao; Yangyang Fan; Yun Liu (Immunity, Inflammation and Disease)
ABSTRACT Background Miscarriage is a common complication of pregnancy, and its underlying pathophysiologic mechanisms remains unclear. The platelet‐to‐lymphocyte ratio (PLR), a prothrombotic and inflammatory marker, has been controversially discussed as a potential predictor of miscarriage. This systematic review and meta‐analysis aimed to assess the predictive significance of the PLR in women with miscarriage compared to healthy pregnancies. Material and Methods Relevant studies were systematically searched in PubMed, Embase, Web of Sciencey, and Cochrane Library up to December 31, 2023. A systematic review and meta‐analysis following PRISMA guidelines was conducted. Articles were identified, screened, and evaluated for quality to determine the predictive value of PLR for miscarriage. Results Fourteen eligible articles, comprising a total of 3745 patients, were included in the meta‐analysis. The pooled analysis found comparable PLR levels between miscarriage and non‐miscarriage groups (SMD = 0.25; 95% Confidence Interval (CI): −0.05 to 0.54). Subgroup analysis revealed significant differences in PLR levels in the missed miscarriage group (SMD = 0.29; 95% CI: 0.01–0.56). and in studies with sample sizes smaller than 200 (SMD = 0.31; 95% CI: 0.05–0.56). Other subgroups did not exhibit significant differences. Subgroup analysis of PLR levels and miscarriage risk demonstrated no significant differences across all subgroups. Conclusion PLR is not a reliable predictor of miscarriage in general. However, for missed miscarriage cases, elevated PLR levels may serve as a practical and cost‐effective marker for prediction.